Giving Children Hope: A Treatment Model for High-Conflict Separation Families - Rauh, Steve; Irwin, Paige; Vath, Nicole (Canadian Journal of Counselling and Psychotherapy, 2016)
This article describes Giving Children Hope, a group treatment program for high-conflict separating families. It begins with a definition of high-conflict divorce, some of the research regarding its impact on children, and its prevalence. The article then describes the development of the program in Winnipeg, Manitoba, and the program structure. Several case examples and a summary of the program evaluation are provided. The article concludes with a discussion of the program’s effectiveness and limitations.